Patient experiences of an ankle fracture and the most important factors in their recovery: a qualitative interview study - Rebecca Samantha Kearney; Rebecca McKeown; David R Ellard; Zi Heng Liew (BMJ Open)
Objective The objective of this qualitative research study is to explore patient experiences of ankle fracture and the factors most important to them in recovery.Design Semistructured interviews exploring patient experiences of ankle fracture recovery at 16–23 weeks following injury. Interviews followed a topic guide and were recorded with an encrypted audio recorder and then transcribed verbatim. Thematic content analysis was used to identify themes in the data.Setting Individuals were recruited from a sample of participants of a UK-based clinical trial of immobilisation methods for ankle fracture (ISRCTN15537280 at the pre-results stage at time of writing). Interviews were conducted at the participants’ own homes or on a university campus setting.Participants A purposive sample was used to account for key variables of age, gender and fracture management. Participants recruited from the clinical trial sample were adults aged 18 years or over with a closed ankle fracture.Results Ten participants were interviewed, five of whom were female and six of whom needed an operation to fix their ankle fracture. The age range of participants was 21–75 years with a mean of 51.6 years. Eight themes emerged from the data during analysis; mobility, loss of independence, healthcare, psychological effects, social and family life, ankle symptoms, sleep disturbance and fatigue, and activities of daily living. Factors of importance to participants included regaining their independence, sleep quality and quantity, ability to drive, ability to walk without walking aids or weight-bearing restrictions, and radiological union.Conclusions The results of this research demonstrates the extensive impact of ankle fracture on individuals’ lives, including social and family life, sleep, their sense of independence and psychological well-being. The results of this study will enable an increased understanding of the factors of relevance to individuals with ankle fracture, allowing collection of appropriate outcomes in clinical studies for this condition. Ultimately these results will help formulate appropriate patient-centred rehabilitation plans for these patients.Trial registration number ISRCTN15537280; Pre-results